SINTESIS NANOPARTIKEL EKSTRAK KULIT MANGGIS MERAH DAN KAJIAN SIFAT FUNGSIONAL PRODUK ENKAPSULASINYA - Nurmalia Ningsih; Sedarnawati Yasni; Sri Yuliani (Jurnal Teknologi dan Industri Pangan, 2017)
Utilization of mangosteen fruit waste tends to be less practical, so nanoparticle based encapsulation is an effective approach. The objective if this research was to utilize the waste from the red mangosteen peel Garcinia forbesii (GF) and Garcinia mangostana (GM) to produce nanoparticle extract, its encapsulation products, and determine its functional properties. This research consists of three stages: extraction, synthesis of nanoparticle, and encapsulation. The parameters evaluated were the yield of extracts, antioxidant, total phenolic content (TPC), particle size, index of polydispersity, and surface morphology of the encapsulated product. Synthesis of nanoparticles was carried out by using ionic gelation method. The functional values was calculated based on  10% extracts  in the nanoparticles solution. The results showed that extraction by reflux method gave better results than that with maceration. Formula of nanoparticles containing 0.2% of chitosan concentration and 0.1% STPP and products encapsulated  with casein and maltodextrine gave the best result with increased functional values.